2012
DOI: 10.4103/0974-8520.100329
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antibacterial and antifungal activities of Cassia fistula Linn. fruit pulp extracts

Abstract: Aim of the study is to assess the antimicrobial activity Cassia fistula fruit pulp extracts on some bacterial and fungal strains. Hydro alcohol and chloroform extracts of Cassia fistula fruit pulp were evaluated for the potential antimicrobial activity. The antimicrobial activity was determined in both the extracts using the agar disc diffusion method. Extracts were effective on tested microorganisms. The antibacterial and antifungal activities of solvent extracts (5, 25, 50, 100, 250 μg/mL) of C. fistula were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…Several investigations have demonstrated the antibacterial effects of fruits on S. pyogenes in vitro. A previous study showed that crude extracts of C. fistula fruit exhibited moderate to strong antibacterial activity against S. pyogenes (23). Another study showed that a novel anti-bacterial peptide, brucin, which is specific to S. pyogenes was produced from the dried fruit protein of Brucea javanica (24).…”
Section: Discussionmentioning
confidence: 99%
“…Several investigations have demonstrated the antibacterial effects of fruits on S. pyogenes in vitro. A previous study showed that crude extracts of C. fistula fruit exhibited moderate to strong antibacterial activity against S. pyogenes (23). Another study showed that a novel anti-bacterial peptide, brucin, which is specific to S. pyogenes was produced from the dried fruit protein of Brucea javanica (24).…”
Section: Discussionmentioning
confidence: 99%
“…Also Cassia fistula is also being used in treating a variety of GIT maladies of bovines; particularly, it is effective in treating E. coli infections effectively. This activity may be due to the presence of several compounds of pharmacological importance including terpenoids, saponins, steroids, anthraquinone, phenolic compounds, and steroids present in them [36]. Similarly seeds of the Foeniculum vulgare are mixed with the root of Glycyrrhiza glabra, and they are also used to treat the GIT infections [37,38].…”
Section: Using Antibiotic Alternativesmentioning
confidence: 99%
“…Various parts of C. fistula have displayed pharmacological properties [17]. The flower, seed, fruit and pulp have been used to treat skin diseases including leprosy [18]. The pulp has been recognized for its antidiabetic properties [15] and has been used in a tonic that has been applied in treatments of gout and rheumatism [19].…”
Section: Introductionmentioning
confidence: 99%